Solar disinfection of drinking water protects against cholera in children under 6 years of age. Issue 4 (1st October 2001) - Conroy, R M; Meegan, M E; Joyce, T; McGuigan, K; Barnes, J
Abstract : BACKGROUND AND AIMS: We have previously reported a reduction in risk of diarrhoeal disease in children who used solar disinfected drinking water. A cholera epidemic, occurring in an area of Kenya in which a controlled trial of solar disinfection and diarrhoeal disease in children aged under 6 had recently finished, offered an opportunity to examine the protection offered by solar disinfection against cholera. METHODS: In the original trial, all children aged under 6 in a Maasai community were randomised by household: in the solar disinfection arm, children drank water disinfected by leaving it on the roof in a clear plastic bottle, while controls drank water kept indoors. We revisited all households which had participated in the original trial. RESULTS: There were 131 households in the trial area, of which 67 had been randomised to solar disinfection (a further 19 households had migrated as a result of severe drought). There was no significant difference in the risk of cholera in adults or in older children in households randomised to solar disinfection; however, there were only three cases of cholera in the 155 children aged under 6 years drinking solar disinfected water compared with 20 of 144 controls. CONCLUSIONS: Results confirm the usefulness of solar disinfection in reducing risk of water borne disease in children. Point of consumption solar disinfection can be done with minimal resources, which are readily available, and may be an important first line response to cholera outbreaks. Its potential in chorine resistant cholera merits further investigation.